Genotyping of 28 blood group alleles in blood donors from Mali: Prediction of rare phenotypes. Issue 2 (April 2016) - Ba, Alhassane; Bagayoko, Seydou; Chiaroni, Jacques; Baiily, Pascal; Silvy, Monique
Abstract: We determined the frequencies of clinically relevant blood group alleles in 300 blood donors from Mali. Multiplex test based on xMAP technology was used to investigate six blood group systems (RH, KEL, MNS, FY, JK, DO, HPA) and complementary analysis were conducted for MNS and RH systems. Polymorphisms that affect the specificity of molecular tests leading to discrepant genotype results are discussed. Antigen expressions were predicted showing that 50% of donors expressed at least one traditional low prevalence antigen, and 11.6% lacked the ability to express at least one high prevalence antigen compatible with Dob-, HPA1a-, S-s-U-, Jsb-, RH:-31 and/or RH:-34 phenotypes.